On determining the width of the accounting strip during ship route accounting of the Caspian seal (Pusa caspica) in shallow water - Baimukanov М.Т.; Iskakova, A.A.; Sydykova, Zh.A.; Baimukanov Т.Т.; Baimukanova А.М. (Fundamental and Experimental Biology, 2022)
In this work, an experimental method for estimating the number of Caspian seals in the sea was tested. The goals were set to determine the distance of visual detection of the Caspian seal in the sea from a small vessel, and to improve the methodology of ship accounting of seals in the Caspian Sea. Ship accounting is used to account for the relative abundance, occurrence and distribution of marine mammals, and the data obtained can also be used as an indicator of accumulations of fish objects, and in general it can indicate the state of the environment. During the period of the vessel’s movement, the length (km) of each daily route is determined, the number of seal encounters on this segment, the distance from the seal to the ship’s line of movement is visually determined. The effective width of the accounting strip and the density ( individuals/km 2 ) in this sec-tion of the sea area are calculated. However, in practice, it is difficult to determine the distance to the ob-served seal when traveling on a small vessel. It is recommended to conduct a route ship registration of seals in shallow water on flat-bottomed boats-budaras. As a result of conducting an experiment in the shallow wa-ters of the Caspian Sea on the visibility of objects imitating the trunk and head of a Caspian seal, it was found that the optimal perpendicular distance from the axis of the accounting route or the optimal width of account-ing from one side is 300 m, similarly, the maximum width of accounting is 550 m. The use of the concepts of optimal and marginal accounting band serves as a method for determining the distance when accounting for seals in the sea and, in the future, for calculating the effective accounting band.